Variability of Nitrogen and Phosphorus Content and Their Forms in Waters of a River-Lake System - Janicka, Ewelina; Kanclerz, Jolanta; Wiatrowska, Katarzyna; Budka, Anna (Frontiers in Environmental Science, 2022)
River-lake systems in Central Europe represent the majority of surface water system forms. In these systems lakes play an important role in river water quality. Published reports on the quality of surface waters in Europe indicate progressive deterioration of their quality, resulting mainly from increasing eutrophication. This study analysed the content of two biogenic elements – nitrogen and phosphorus – and their mineral forms in the Głuszynka river, representative for the river-lake systems of Central Europe. The research was conducted in the hydrological years 2016 - 2018. The ecological status of the Głuszynka river, due to the ‘poor’ status of both biological elements and physicochemical elements (content of phosphorus and nitrogen compounds), was classified as ‘poor’. In the period analysed an increase in the content of nitrogen compounds was recorded in the hydrological year 2018. However, during the growing period a significant decrease in the content of total and nitrate nitrogen was observed, which was related to the activity of primary producers. For phosphorus compounds a slight increase of their content was observed during this period. This was associated with high tourist and recreational pressure on the analysed system. Analysing the spatial variability of biogenic compounds it was observed that along the course of the river the content of nitrite and nitrate nitrogen as well as total nitrogen increased at successive sampling points. An opposite trend of change along the river course was observed for phosphorus compounds (content of P-PO4 and total phosphate decreased by 14% and 15.9%, respectively). Statistical analyses carried out highlighted the relationship between water quality and land use in the direct catchments of lakes included in the river-lake network. Arable land was associated with higher the content of orthophosphorus phosphate, grassland total nitrogen, nitrite and nitrate nitrogen, while urbanisation was strongly associated with ammonium nitrogen.